PROBLEMATIKA ORANG TUA TUNGGAL DALAM MEMENUHI HAK-HAK ANAK (Studi Kasus pada Masyarakat Cikupa Tangerang) - Wafa Amal Khoerina; Muhammad Nurul Fahmi (LPPM STAI Muhammadiyah Probolinggo, 2024)
Abstract A person who manages the household, takes care of the children and themselves without the help or presence of a spouse is called a single parent. Single parents have an important task in fulfilling children's rights. However, every family must have various problems, as well as single parents who live in Cikupa Tangerang. This study aims to analyze and find children's rights in an Islamic perspective, because children's rights in Cikupa are only fulfilled by single parents, and the main obstacles of single parents in Cikupa in fulfilling children's rights. This research uses a qualitative approach with a case study type of research. The results showed that (1) children's rights in the Islamic perspective can be divided into material rights, and non-material rights, (2) the reasons why children's rights in Cikupa are only fulfilled by single parents are due to the death of one of the parents and divorce, (3) the main obstacles of single parents in Cikupa in fulfilling children's rights are obstacles in fulfilling the right to maintenance, obstacles in fulfilling inheritance rights, and obstacles in fulfilling the right to get tarbiyyah, ta'lim, and ta'dib. Keywords: problematics; single parents; children's rights; Islam.